IMPACT OF COMMERCIAL AND INVESTMENT ACTIVITIES IN AGRICULTURE ON LOCAL DEVELOPMENT - Dokić, Aleksa; Užar, Dubravka; Petković, Goran; Stojković, Dragan (Economics of Agriculture, 2020)
The main idea in this paper was to investigate how agriculture and processing sectors are connected through commercial activity, and how they influence municipal economic development in transition economies. This was examined through the influence of relevant non-price structural factors related to agricultural and processing sector on the ratio between agricultural product procurement and overall agricultural production. The focus was placed on agricultural investments and subsidies. A multi regression model was developed based on hard data provided by SORS and SBRE on a municipal level in Serbia. The analysis confirmed the relation between agricultural commercial activity and municipal level of economic development. In addition, important findings concerning municipal investment and agricultural subsidies allocation have been provided as well.